Barriers and facilitators to participation in women's and girls' rugby: a mixed-methods study - Flower, K. D.; Knight, C. J.; Rouquette, O. Y.; Waldron, M.; Barrell, D.; Mumford, E.; Love, T. D. (Journal of Sports Sciences, 2025)
The aim of this study was to identify the perceived barriers and facilitators to participating in the elite women`s rugby pathway in England. An explanatory sequential mixed-method design was adopted comprising a survey and interviews. In total, 1,349 participants completed the survey. Quantitative survey data were analysed using descriptive statistics and Wilson-corrected frequency intervals. Subsequently, interviews were conducted with 46 survey respondents. Qualitative data were analysed using the coding stages recommended by Miles and colleagues (2019). Findings indicate that key facilitators included social support from parents, friends, and support staff within rugby, as well as participants` enjoyment of the game, underpinned by the inclusivity of the sport, all of which contributed to both initial and continued participation. In contrast, barriers included stereotypes associated with the sport, time constraints, limited access at school, and challenges surrounding access to rugby opportunities linked with geographical location and education. The findings underline the complex and interrelated nature of these factors, which varied substantially depending on one`s age, level of playing environment, and geographical location.